STING1 Promotes Ferroptosis Through MFN1/2-Dependent Mitochondrial Fusion - Li, Changfeng; Liu, Jiao; Hou, Wen; Kang, Rui; Tang, Daolin (Frontiers in Cell and Developmental Biology, 2021)
Ferroptosis is a type of iron-dependent regulated cell death caused by the disruption that occurs when oxidative stress and antioxidant defenses interact, and then driven by lipid peroxidation and subsequent plasma membrane ruptures. The regulation of ferroptosis involves many factors, including the crosstalk between subcellular organelles, such as mitochondria, endoplasmic reticulum (ER), lysosomes, lipid droplets, and peroxisomes. Here, we show that the ER protein STING1 (also known as STING or TMEM173) promotes ferroptosis in human pancreatic cancer cell lines by increasing MFN1/2-dependent mitochondrial fusion, but not mitophagy-mediated mitochondrial removal. The classic ferroptosis inducer erastin, but not sulfasalazine, induces the accumulation of STING1 in the mitochondria, where it binds to MFN1/2 to trigger mitochondrial fusion, leading to subsequent reactive oxygen species production and lipid peroxidation. Consequently, in vitro or xenograft mouse models show that the genetic depletion of STING1 or MFN1/2 (but not the mitophagy regulator PINK1 or PRKN) reduces the sensitivity of pancreatic cancer cells to ferroptosis. These findings not only establish a new mitochondrial fusion-dependent cell death mechanism, but also indicate a potential strategy for enhancing ferroptosis-based therapy.